Application of Memetic Algorithms in Multi-Criteria Structural Optimization - Peter Pechac; Milan Saga; Peter Weis; Tomasz Domanski; Marcin Kubiak (Communications - Scientific letters of the University of Zilina, 2017)
The goal of this paper is to present new innovative algorithms for discrete structural optimization of problems involving multi-criteria objective function, which contains stress, displacement and frequency constraints. The algorithm is tested on a shell finite element structure, whose optimization variables are geometrical parameters and shell thicknesses. Performance of memetic algorithm will be compared with genetic algorithm.